‘Safe Spaces’: Experiences of Feminist Women-Only Space - Lewis, Ruth; Sharp, Elizabeth; Remnant, Jenni; Redpath, Rhiannon (Sociological Research Online, 2015)
The gendered nature of safety has been explored empirically and theoretically as awareness has grown of the pervasive challenges to women's safety. Notions of ‘safe space’ are frequently invoked in wider feminist environments (particularly, recently, in relation to debates about trans people's access to women's spaces), but are relatively neglected in academia. Indeed, despite a body of scholarship which looks at questions of gender, safety and space, relatively little attention has been paid to exploring the meaning of ‘safety’ for women and, particularly, the meaning and experience of spaces they consider to be ‘safe.’ Drawing on focus group data with 30 women who attended a two-day, women-only feminist gathering in the UK, this paper analyses experiences of what they describe as ‘safe space’ to explore the significance and meaning of ‘safety’ in their lives. Using their accounts, we distinguish between safe from and safe to, demonstrating that once women are safe from harassment, abuse and misogyny, they feel safe to be cognitively, intellectually and emotionally expressive. We argue that this sense of being ‘safe to’ denotes fundamental aspects of civic engagement, personhood and freedom.
Publisher: SAGE Publications Ltd
Keywords: Activism; Feminism; Safety; Space; Women; Women-Only

Victoria Sets Up Taskforce To Tackle Harassment Of Women At Gigs (Tone Deaf, 2015)
Following a meeting of the Victorian Live Music Roundtable yesterday, Victorian Minister for Consumer Affairs, Gaming and Liquor Regulation Jane Garrett

All the girls in town: The missing women of Australian rock, cultural memory and coverage of the death of Chrissy Amphlett - Strong, Catherine (Perfect Beat, 2015)
This article will use the cultural and media materials produced around the death of Chrissy Amphlett as a way of interrogating the fact that surprisingly few resources exist that document or commemorate the contribution of women to the rock music scene in Australia. As Amphlett is unusual in being a woman who has, even before her death, claimed a place in the Australian rock canon, examining materials that are designed to construct her legacy upon her passing will provide examples of how women in Australian rock are discussed. It will be demonstrated that Amphlett’s gender is central to these discussions, and that she is used to both obscure the contributions of other women performers and to deny a need for women musicians to even be an object of discussion at all. These indings will be analysed using Aleida Assmann’s concepts of functional and storage memory, and it will be argued that the lack of information that we have about past female rockers makes it harder for women in Australia to see this ield as one they can participate in, and also makes the retention of memories about currently successful women musicians less likely.

Pathways to Help: Adolescent Sexual Assault Victims’ Disclosure and Help-Seeking Experiences - Campbell, Rebecca; Greeson, Megan R.; Fehler-Cabral, Giannina; Kennedy, Angie C. (Violence Against Women, 2015)
In this study, we conducted semistructured interviews with N = 20 adolescent sexual assault victims who sought postassault help from the medical and legal system to understand young survivors’ disclosure and help-seeking processes. Results revealed three distinct disclosure patterns and pathways to help-seeking. First, in the voluntary disclosure group, victims told their friends, who encouraged them to tell an adult, who then encouraged—and assisted—the survivors in seeking help. Throughout this process, the survivors’ disclosures at each step were within their control and reflected their choices for how to proceed. Second, in the involuntary disclosure pattern, victims also first disclosed to friends, but then those friends told adults about the assault, against the survivors’ wishes; the adults made the victims seek help, which was also against the survivors’ preferences. Third, in situational disclosures, the survivors were unconscious at the time of the assault, and their friends disclosed and sought help on their behalf. We also examined how these initial disclosure patterns related to victims’ continued engagement with these systems.
Publisher: SAGE Publications Inc
Keywords: adolescents; disclosure; help-seeking; rape; sexual assault

Cultural Value and Inequality: A Critical Literature Review - Oakley, K; O'Brien, D (2015)
Inequality has become essential to understanding contemporary British society and is at the forefront of media, political and practice discussions of the future of the arts in the UK. Whilst there is a wealth of work on traditional areas of inequality, such as those associated with income or gender, the relationship between culture, specifically cultural value, and inequality is comparatively under-researched. The literature review considers inequality and cultural value from two points of view: how cultural value is consumed and how it is produced. The review argues that these two activities are absolutely essential to understanding the relationship between culture and social inequality, but that the two activities have traditionally been considered separately in both academic research and public policy. The review concentrates on the ‘big three’ issues of inequality – race, class and gender, where most of the literature is to be found, but also touches on disability, sexuality and spatial inequality. All of the research reviewed suggests an undeniable connection between cultural value and inequality. Understanding that connection is currently impeded by problems with data. The report suggests the political saliency of this topic means that public policy must do more to provide robust research, particularly about cultural production.

Sex, Gender and Work Segregation in the Cultural Industries - Hesmondhalgh, David; Baker, Sarah (The Sociological Review, 2015)
This chapter addresses work ‘segregation’ by sex in the cultural industries. We outline some of the main forms this takes, according to our observations: the high presence of women in marketing and public relations roles; the high numbers of women in production co-ordination and similar roles; the domination of men of more prestigious creative roles; and the domination by men of technical jobs. We then turn to explanation: what gender dynamics drive such patterns of work segregation according to sex? Drawing on interviews, we claim that the following stereotypes or prevailing discourses, concerning the distinctive attributes of women and men, may influence such segregation: that women are more caring, supportive and nurturing; that women are better communicators; that women are ‘better organized’; and that men are more creative because they are less bound by rules.
Publisher: SAGE Publications Ltd
Keywords: cultural industries; sexual division of labour; stereotypes; work segregation

Resilience & Melancholy: Pop Music, Feminism, Neoliberalism - James, Robin (John Hunt Publishing, 2015)
When most people think that “little girls should be seen and not heard,” a noisy, riotous scream can be revolutionary. But that’s not the case anymore. (Cis/Het/White) Girls aren’t supposed to be virginal, passive objects, but Poly-Styrene-like sirens who scream back in spectacularly noisy and transgressive ways as they “Lean In.” Resilience is the new, neoliberal feminine ideal: real women overcome all the objectification and silencing that impeded their foremothers. Resilience discourse incites noisy damage, like screams, so that it can be recycled for a profit. It turns the crises posed by avant-garde noise, feminist critique, and black aesthetics into opportunities for strengthening the vitality of multi-racial white supremacist patriarchy (MRWaSP). Reading contemporary pop music – Lady Gaga, Beyonce, Calvin Harris – with and against political philosophers like Michel Foucault, feminists like Patricia Hill Collins, and media theorists like Steven Shaviro, /Resilience & Melancholy/ shows how resilience discourse manifests in both pop music and in feminist politics. In particular, it argues that resilient femininity is a post-feminist strategy for producing post-race white supremacy. Resilience discourse allows women to “Lean In” to MRWaSP privilege because their overcoming and leaning-in actively produce blackness as exception, as pathology, as death. The book also considers alternatives to resilience found in the work of Beyonce, Rihanna, and Atari Teenage Riot. Updating Freud, James calls these pathological, diseased iterations of resilience “melancholy.” Melancholy makes resilience unprofitable, that is, incapable of generating enough surplus value to keep MRWaSP capitalism healthy. Investing in the things that resilience discourse renders exceptional, melancholic siren songs like Rihanna’s “Diamonds” steer us off course, away from resilient “life” and into the death.
Keywords: Bibliographie; Music / History & Criticism; Nettoyer; Philosophy / Social

The Economic and Cultural Value of Live Music in Australia 2014 - Carter, D. (2015)
The Economic and Cultural Value of Live Music in Australia 2014

Gender and creative labour - Conor, B; Gill, R; Taylor S (The Sociological Review, 2015)
Keywords: gender inequality; neoliberalism; precariousness; self-representation; sexism